(untitled) (Khairulummah, 2022)
The art of biography is one of the finest and highest arts in importance and status, as it sometimes reveals the cultural features that man seeks and preserves the history of nations and the conditions of ages. The biography is divided into two types: 1) General biography 2) Private biography The general biography: It deals with the lives of many people, and is intended for books of biographies, classes, and news. Private biography: It is of two types, self and other 1) Autobiography: It revolves around the life of its writer, and it is a personal experience of an individual, where the individual himself writes his history, records his events and news, and lists his works and effects, and the days of his childhood, youth and old age, and the important events that happened to him in it - and it is called in Urdu "Aap Betty" 2) Altruistic biography: It is a story related to the life of a person who left an impact on life that attracted him to history, and reveals the secret of his genius and uniqueness. In this regard, the Arabic is the fragrant biography of the Prophet, then the biography of the first in command and literature - and it is called in Urdu literature "Sawah Amri"